Difficulty analysis of numerical ability of indigenous Papuans (Marind and Kanum Tribes) in Yanggandur and Wasur Villages, Merauke Regency - Andi Sitti Suhartini; Indah Widanarti; Elah Nurlaelah; Siti Fatimah (Journal of Advanced Sciences and Mathematics Education, 2022)
Mathematics is one of the subjects that provides the provision of reasoning needed to become a quality human being. Counting is a very small part of mathematics, but it is very important. This study aims to analyze the difficulties in numeracy of the Marind and Kanum tribal communities in Yanggandur and Wasur Villages, Merauke Regency. The methods used are literature study and observation. The results of the study show that the Marind and Kanum tribes have difficulty calculating operations in large numbers because most of the people's daily lives do not use large numbers of addition and subtraction operations, namely hunting and fishing. The community also has staple foods, namely kumbili and sago, which are obtained from their own villages so that there are no transactions that require large amounts of calculation.